2014
DOI: 10.5430/wje.v4n2p37
|View full text |Cite
|
Sign up to set email alerts
|

Development of Examination Behaviour Inventory: An Integrity Measure for Prevention of Cheating in School Exams

Abstract: Cheating in examinations is an educational menace that has threatened the very essence of schooling in most countries of the world. Therefore, it has become imperative for researchers in education to seek alternative strategies for curbing it in order to restore the dignity of school examinations as an instrument for assessing actual educational attainment by students. This research study addresses this challenge by developing an inventory that could be used to measure the examination behaviour of prospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…Similar findings were also observed between male and female academic achievements of medical students during undergraduate studies but a slight shift in pediatrics and surgery as the females performed better than their male counterparts Albalawi, 43 Eya & Ezeh. 44 Meanwhile, Ossai et al, 45 believed age and gender significantly influence the academic performance of students especially females, when Academic Integrity is considered, females outperformed males while as the age of the student increases, the poorer the academic performance. To ensure diversity in Engineering studies, the study suggested the need to increase the participation of females in Engineering programmes as females constitute 12.9% of the population of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were also observed between male and female academic achievements of medical students during undergraduate studies but a slight shift in pediatrics and surgery as the females performed better than their male counterparts Albalawi, 43 Eya & Ezeh. 44 Meanwhile, Ossai et al, 45 believed age and gender significantly influence the academic performance of students especially females, when Academic Integrity is considered, females outperformed males while as the age of the student increases, the poorer the academic performance. To ensure diversity in Engineering studies, the study suggested the need to increase the participation of females in Engineering programmes as females constitute 12.9% of the population of the study.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the three original elements of Theory of Planned Behaviour [TPB] (Ajzen, 2006) which comprised of Attitude towards Behaviour (ATB), Subjective Norms (SN) and Perceived Behavioural Control (PBC) could be influenced by demographic factors, moral obligation and moral reasoning because the phenomenon of academic dishonesty is not just a spontaneous event but an activity that is planned, coordinated and executed. That being the case, it is, therefore, possible to measure the tendency or propensity of an individual to engage in the act of examination malpractices as demonstrated by Ossai et al (2014;2020; where inventories for measuring examination behaviour of students at the secondary school and tertiary educational institutions levels were developed. Scores from these measurements are the bedrock of the proactive framework for preventive actions against examination malpractices in schools.…”
Section: Discussionmentioning
confidence: 99%
“…The strategies adopted by the examination bodies to curb examination malpractices seems to have limited success hence it is imperative for academics to discover other means of tackling this educational monster. New measures such as determination of the propensity of a candidate to engage in examination malpractices so as to checkmate it, is the emerging strategy (Madara, Namango & Katana, 2016;Zanon, Hutz, Yoo & Hambleton, 2016;Ossai, 2018;Ossai et al 2014Ossai et al , 2020Ossai et al , 2023. One dimension of the preventive approach is to devise a means of measuring the propensity of a candidate to either engage or disengage in the act of cheating in examinations.…”
Section: Justification For the Studymentioning
confidence: 99%
“…Kredibilitas UN menjadi hal penting untuk dilihat karena sebagai bentuk pemeriksaan tindak kecurangan pada saat UN (Adow, Alio, & Thinguri, 2015). Jika tindak kecurangan pada saat penyelenggaraan UN semakin tinggi, maka semakin mengikis kredibilitas UN (Ossai, Ethe, Okwuedei, & Edougha, 2014).…”
unclassified